STUDYOF THE REACTION OF CARDIOVASCULAR SYSTEM ON PHYSICAL ACTIVITYIN SCHOOLPUPILS AGED 11–14 YEARS WITH VISION PATHOLOGY - T. V. Pavlova; N. B. Pilkevich; V. V. Dychko (Медицинский вестник Юга России, 2017)
Objective: to study the reaction of the cardiovascular system on physical activity in school pupils aged 11-14 years with vision pathology.Materials and methods: the study was conducted with the participation of 113 school pupils aged 11-14 years. The main group consisted of 58 blind and poor-sighted children, the control group consisted of 55 healthy. To assess the level of the exchange-energy processes occurring in the body using the index Robinson.Status activityof the autonomic nervous system was evaluated on the index Kerdo.Results: the myocardial oxygen demand is lower in boys withvision pathology of the load at height PWC150 and higher in girls of the same group at the 5th minute of rest than inthe children of the same age in terms of healthy. Kerdo index in children of the main group was higher than in healthy and pointed to the significant prevalence of the activity of the sympathetic nervous system (SNS). Endurance factor in children with vision pathology,regardless of gender, to the load and on the 1st, 5th min rest did not significantly differ from the healthy group.Robinson index during exercise in boys with vision pathologywasof lower and girls in the same group is higher than the children of the same age in terms of healthy.The minute volume of blood (MVB), mean arterial pressure (MAP) at rest was substantially higher and lower load in children with vision pathology.Conclusions: school pupils with vision pathology of predominant activity of the sympathetic nervous system, reduced Robinson index, minute volume of blood and mean arterial pressure, minor violations of the activity of the cardiovascular system.